Characterization and optimization of novel surface-enhanced Raman scattering (SERS)-based nanoimaging probes for chemical imaging - Hankus, Mikella E.; Gibson, Gregory J.; Cullum, Brian (SPIE, 2005)
We have developed a novel class of surface-enhanced Raman scattering (SERS)-based nanoimaging probes for chemical imaging with nanometer scale spatial resolution. Using these SERS nanoimaging probes it is possible to differentiate between different chemical components within the sample under analysis. These SERS nanoimaging probes are fabricated from coherent fiber optic imaging bundles composed of 30,000 individual image transmission elements. Using a specially programmed micropipette puller, the individual fiber elements are uniformly heated and pulled, creating a tapered bundle with a flat tip. In order to create the SERS active surface, the tapered end of the fiber bundle is roughened on the "molecular scale" via chemical etching, and is then over-coated with silver in a controlled manner via vapor deposition in a vacuum evaporator. Following etching, six regularly spaced peaks are produced surrounding each of the individual image transmission elements of the bundle, and it is these peaks onto which the metal over-layer is deposited. Due to the high degree of uniformity in the surface of these tapered and etched tips, these SERS nanoimaging probes exhibit significantly greater reproducibility than SERS substrates fabricated through similar silver film over nanostructure fabrication processes. Characterization and optimization of these SERS nanoimaging probes using SERS active chemicals is discussed.
Optics East 2005, 23-26 OCTOBER 2005, Boston, MA, United States